2021
DOI: 10.1093/jscr/rjab403
|View full text |Cite
|
Sign up to set email alerts
|

Use of electrochemotherapy in a combined surgical treatment of local recurrence of rectal cancer

Abstract: Recurrence of rectal cancer (RRC) affects up to one-third of patients. The survival is strictly dependent on the possibility of performing surgery without microscopic tumor residues (R0). Electrochemotherapy (ECT) is based on the effect that electric pulsations have on increasing the permeability of the cell membrane to certain drugs. We propose the association of ECT to the surgical excision of perineal RRC in a 72-year-old male patient. Given the proximity between the recurrence and the urethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to various authors, about 18-32% of newly identified malignant neoplasms of the pelvic organs are locally widespread. This extent of spread can lead to the refusal of radical surgery and the prescription of palliative therapy, resulting in a total life expectancy of 1 to 6 months [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…According to various authors, about 18-32% of newly identified malignant neoplasms of the pelvic organs are locally widespread. This extent of spread can lead to the refusal of radical surgery and the prescription of palliative therapy, resulting in a total life expectancy of 1 to 6 months [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important positions is the zone of the primary location of the tumor, its volume, and direction/deepness of invasion. Moreover, the radicality of the performed surgical intervention affects the risk of recurrence and the need for reoperation [ 1 , 2 ]. All this determines the need for an accurate preoperative and intraoperative visualization of both the tumor itself and the anatomical structures surrounding it, taking into account their topography and the individual characteristics of the patient, especially if there was a previous surgical intervention in this anatomical zone [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%